O problema de “chutar o balde” do português brasileiro para a língua inglesa na ótica da semântica enunciativa: a construção do significado para além da combinação de palavras - Bastos, Karla Priscila Machado (Universidade Federal de São Carlos, 2025)
This work addresses the challenges and limitations of the literal translation of idiomatic expressions (IEs) from Brazilian Portuguese (BP) into English in the light of Enunciative Semantics. The main objective is to investigate the shifts in meaning that result from a literal translation of these expressions, considering the enunciation as a singular event in which the subject mobilizes memories and projects future interpretations. To this end, the study takes IE "kicking the bucket" as its subject and compares the meanings generated by automatic translation (AT) tools such as Google Translator with the meanings that emerge in collaborative enunciation spaces such as the English Experts Forum. The study has shown that ATs work with a formalistic and decontextualized approach, ignoring the historicity and enunciative scene in which the expression occurs. In turn, collaborative translations mobilize memories and incorporate cultural and social elements that contribute to a more accurate interpretation of the original meaning. The analysis shows that literal translation often leads to ambiguity and loss of meaning, which emphasizes the need to take into account the discursive, historical, and ideological aspects that intersect the construction of meaning. Finally, the study offers didactic suggestions for foreign language teaching by emphasizing the importance of integrating EIs into real contexts of enunciation exploring the different possibilities of interpretation, thus contributing to an approach to translation that respects the heterogeneity of meanings and promotes greater cultural integration between languages and subjects.
The problem of "chutar o balde" from brazilian portuguese into english from the viewpoint of enunciative semantics: constructing meaning beyond the word combination
Keywords: Semântica; Enunciação; Tradução; Expressão idiomática; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA